Optimization of microwave assisted extraction from Rhodomyrtus tomentosa fruits using response surface methodology. (February 2019) - Ridlo, M; Kumalaningsih, S; Pranowo, D
Abstract: Rhodomyrtus tomentosa (Ait.) Hassk include in the horticulture products with superior bioactive compounds. The benefit of fruit parts has been used as traditional herbs in Malaysia, Vietnam, Thailand and China. In this research, bioactive compounds from Rhodomyrtus tomentosa were obtained by Microwave Assisted Extraction (MAE). MAE is a modern extraction method that used microwaves to enhancement the effectivenesss and efficiency of cell rupture. The optimum result of extraction process determined by Response Surface Methodology (RSM) toward the extract yields, total anthocyanins content and total flavonoids content. Based on ANOVA test results, there is a significant influences on each responses with p-value<0.05. The p-value of the lack of fit in each responses has an insignifant influence (p-value>0.05) which means the model can be used as an optimization predictions. The optimum conditions for MAE process were 190 seconds of extraction times and 1:19.05 (w/v) of sample to solvents ratio. The verification of optimum condition are 1.07% of extract yields, 3.78 mg/g of anthocyanins and 15.47 mg/g of flavonoids, which all of responses are in the threshold of the predicted value.